Hubungan Antara Risiko Kardiovaskuler dengan Fungsi Kognitif pada Lansia di Kartasura - Sulistyani Sulistyani; Yusuf Alam Romadhon (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Cardiovascular disease is still a major public health problem. The Indonesian population is an aging population, and the number of dementia cases is increasing. A good understanding of the correlation between the risk of cardiovascular disease and dementia will increase the accuracy in the long-term prevention of dementia in the community. This study was intended to examine the correlation between cardiovascular risk and early signs of dementia. 89 elderly integrated health center participants were voluntarily involved in this study. This research is a cross-sectional design. Respondents were measured for cardiovascular risk, using the Jakarta Cardiovascular Score (SKJ) and measuring cognitive function using the Mini-Mental State Examination (MMSE). Statistical analysis using correlation and mean difference. There is a negative correlation between the Jakarta Cardiovascular Score and the MMSE score (r=-0.311; p=0.003). In the analysis of mean differences, it was found that there was a significant difference between mild, moderate, and high cardiovascular risk in cognitive decline (MMSE score) respectively, the MMSE mean [27.29; SD=3.51], [25.55; SD=5.42], and [24.82; SD=4.51]; with p-value = 0.010. There is an inverse correlation between cardiovascular risk and cognitive function, statistically significant